2014
DOI: 10.2478/s13386-013-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating similarity of radial increments around tree stem circumference of European beech and Norway spruce from Central Europe

Abstract: Extracting cores from a tree using an increment borer has been standard practice in dendrochronological studies for a long time. Although empirical rules exist regarding how many samples to take and which methodology to apply, comparatively few studies provide quantification of the similarity of relative tree-ring-widths (TRW) around the stem circumference. The aim of this study was therefore to precisely measure the similarity of standardised TRWs around the stem circumference and to provide objective suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Weather data from our study area from 1950 onwards suggested that the climatic conditions for beech trees in the area investigated changed dramatically during this period. Roughly estimating the tree age from their trunk circumference ( Bošeľa et al, 2014 ), more than a third of the trees were already in place at the beginning of this period. About 60% were recruited prior to the acceleration of temperature change from the 1980s onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Weather data from our study area from 1950 onwards suggested that the climatic conditions for beech trees in the area investigated changed dramatically during this period. Roughly estimating the tree age from their trunk circumference ( Bošeľa et al, 2014 ), more than a third of the trees were already in place at the beginning of this period. About 60% were recruited prior to the acceleration of temperature change from the 1980s onwards.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were extracted using a Pressler borer at breast height. Because the between-tree variability within a site is much higher than the within-tree variability around the stem (Bošeľa et al, 2014), one core per tree was extracted. Likewise Fritts (1976) suggested that for climate studies, one core per tree is sufficient if more than 14 trees are sampled.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, fifteen to forty-two dominant, co-dominant and sub-dominant trees were selected in the C and T plots at each of the four sites selected for this research (Table 1). One core was taken from each selected tree using Pressler increment borer (Bosela et al, 2014), perpendicular to the slope of the site, generating a total of 179 tree-ring-width (TRW) series. Core samples were air-dried and sanded to increase the visibility of annual tree rings; their widths were established at 0.001 mm resolution using the LINTAB (RINNTECH.…”
Section: Tree Ring Sampling and Climate Datamentioning
confidence: 99%